KAJIAN BIBLIOMETRIK: KOLABORASI PENULIS PADA JURNAL ILMU PERPUSTAKAAN TERAKREDITASI SINTA 2 PERIODE 2019-2023 - Eko Noprianto (JURNAL ILMU PERPUSTAKAAN (JIPER), 2024)
The aim of this research is to investigate author collaboration in library science journals accredited SINTA 2 (BIP, BACA, Khizanah, and JKIP) from 2019 to 2023, which includes the growth of articles with collaborative authorship, the level of collaboration, and collaboration index. This study applies bibliometric methods, which involve measuring authorship in a scholarly publication. Research data were collected by directly accessing the respective journal websites, and the data were processed using MS Excel to create tables and perform necessary statistical calculations.Based on the search results, 390 articles were found during the period of 2019-2023. These articles are distributed among the journals as follows: 108 articles in the BIP journal, 92 articles in the BACA journal, 114 articles in the Khizanah journal, and 76 articles in the JKIP journal. Data analysis results indicate that in the BIP, JKIP, and Khizanah journals, almost all articles were written with collaborative authorship, while in the BACA journal, only the majority of articles were written with collaborative authorship. The collaboration level values obtained for the journals are as follows: BIP journal: 0.81, BACA journal: 0.73, Khizanah journal: 0.76, and JKIP journal: 0.80, while the collaboration indices for BIP journal is 1.96, BACA journal is 1.86, Khizanah journal is 2.08, and JKIP journal is 2.25.The conclusion of this research is that articles with collaborative authorship are more frequently published bylibrary science journals accredited SINTA 2.